How to Manage a Bully: Workplace Bullying in Construction - McKay, Ruth (Advances in Social Sciences Research Journal, 2016)
Workplace bullying is industry specific. Organizations need to evaluate what is acceptable and unacceptable behaviour in their industry and among their workers in order to make organizational policies effective and respected. This paper looks at workplace bullying in the construction industry. The paper considers how employees, specifically site superintendents, working in construction view workplace bullying and view the best ways for dealing with workplace bullying. The data examined in this paper is drawn from an online forum for construction site superintendents. The comments by the site superintendents reveal how workplace bullying is dealt with on construction sites and how workplace bullying policies are viewed.